Does INDONESIAN CAPITAL MARKET EFFICIENT?: A RELATION BETWEEN PRICE-VOLUME - Asnawi, Said Kelana; Pratama, Samuel; Kurniawan, Hans Christian; Rodjana, Samuel Yosua (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
Efficient markets show prices have reflected information. In an efficient market, the pattern of price movements is a random walk, meaning that prices cannot be predicted accurately, so investors do not get abnormal returns. The informations used in this study are: lag-return (r-1); lag return(r-2); trading volume, as well as the synergy between (r-1) and trading volume. This research found that the coefficient was not significant in almost all tests. Investors cannot use past information to get abnormal returns Thus the efficient market hypothesis is proven. This efficient market situation shows that all market participants have equal opportunities in terms of risk-return.